Implementation of problem-solving learning model assisted by student worksheets to improve critical thinking skills in the context of reaction rate - Nadhifa Is'ad; Sukarmin Sukarmin (Jurnal Pijar Mipa, 2022)
This research aims to describe the implementation of the problem-solving learning model, students' activities, critical thinking skills, learning outcomes, and students' responses toward learning model implementation. Methods of the research used are pre-experimental with one group pretest-posttest design. The research subjects were 36 students of class 11th grade MIPA 1 at Senior High School 19 Surabaya, Indonesia. It is found that the problem-solving learning model was implemented during two meetings obtained an average percentage of 96.57% and 98.68%. Secondly, students' relevant activities for enhancing critical thinking skills during two meetings received 96.24% and 97.61%. Thirdly, critical thinking skills on the four indicators have increased in the high criteria as the N-gain score represents for the interpretation indicator is 0.86, analysis is 0.75, evaluation is 0.86, and inference is 0.89. Fourth, student learning outcomes classically get a percentage of 97.22%. Fifth, students give positive responses to implementing the problem-solving learning model assisted by student worksheets with a responses percentage of 94.61%. The result represented that the problem-solving learning model assisted by student worksheets can train students' critical thinking skills on reaction rate material.